Strategi Peningkatan Kecerdasan Sosial Emosional Anak Melalui Metode Bermain Peran di RA Al-Manar Lembung Timur Lenteng Sumenep - Fika Fitrotin Karomah; Ali Rahmat (Kariman: Jurnal Pendidikan Keislaman, 2023)
This study aims to understand the emotional social intelligence of children, role-playing techniques in enhancing emotional social intelligence, and to determine the level of children's emotional social development after implementing role-playing strategies. This research was conducted due to several issues concerning children's emotional social intelligence. The research design employed is a classroom action research (CAR) using the Kurt Lewin model. Data collection methods involved observation, interviews, and documentation. Data analysis was conducted over 2 cycles, each cycle consisting of four stages: planning, implementation, observation, and reflection. The success criterion set was met if a minimum of 80% of 15 children exhibited emotional social intelligence with criteria indicating significant improvement. The result indicate that children's emotional social intelligence, when developed through role-playing methods using indicators such as willingness to share, collaborate, and patiently wait for turns, showed improvement. The pre-action observation revealed a 6.67% rate, signifying that children's emotional social intelligence was significantly below the predefined success indicators. In Cycle I, there was a 26.67% increase, though not yet meeting the established success indicators. In Cycle II, the rate reached 86.67%, indicating that emotional social intelligence in group B2 reached the 80% success indicator threshold, leading to the conclusion of the research study.